GE_GERICHTE P/21374/2017 vom 19. Dezember 2017 - GE Cour de justice (2017)
DOCUMENT INTERNE ; BANQUE ; CALOMNIE ; DIFFAMATION ; INFRACTIONS CONTRE LA LIBERTÉ | CPP.310.ala; CPP.310.alc; CP.173; CP.174